2002
DOI: 10.2135/cropsci2002.0365
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Inbred Lines Capable of Improving Ear and Stover Yield and Quality of Superior Silage Maize Hybrids

Abstract: should also be practiced on whole-plant digestibility (Barriè re et al., 1997). Stover is as important as the ear Maize (Zea mays L.) is an excellent feed, whether fresh, chopped, because it contributes half of dry matter yield. Roth et or ensiled. Silage maize hybrids have been developed for temperatecold regions of Europe and North America, but limited research al. (1970) suggested that silage maize is primarily a high has been done to develop silage hybrids for temperate and warm-energy feed, and that its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…For example, Waldron et al (2002) used it to study stability of yield of cool-season pasture grasses; Gravois and Helms (1998) and Gravois and Bernhardt (2000) used yield stability statistic to select rice cultivars for seed yield and seed quality, respectively; Fan et al (2007) evaluated grain yield stability of maize hybrids; Upadhya and Cabello (2000) evaluated the stability of potato seed families; Baxevanos et al (2008) reported very high repeatability of yieldstability statistic in multi-environment trial of cotton cultivars; Rao et al (2002) used of YS i to select foodgrade soybean genotypes for some agronomic traits, e.g., plant height, seed weight, biomass, seed yield, and harvest index. In addition, Bertoia et al (2002) used of YS i to identify superior maize hybrids on the basis of forage yield and stability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Waldron et al (2002) used it to study stability of yield of cool-season pasture grasses; Gravois and Helms (1998) and Gravois and Bernhardt (2000) used yield stability statistic to select rice cultivars for seed yield and seed quality, respectively; Fan et al (2007) evaluated grain yield stability of maize hybrids; Upadhya and Cabello (2000) evaluated the stability of potato seed families; Baxevanos et al (2008) reported very high repeatability of yieldstability statistic in multi-environment trial of cotton cultivars; Rao et al (2002) used of YS i to select foodgrade soybean genotypes for some agronomic traits, e.g., plant height, seed weight, biomass, seed yield, and harvest index. In addition, Bertoia et al (2002) used of YS i to identify superior maize hybrids on the basis of forage yield and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Maize grain has a digestible energy (DE) content much higher than maize stover and it is assumed that the quality of forage maize is determined only by the ear to stover ratio, but this trait does not adequately predict the nutritional value of maize (Bertoia et al, 2002). Due to its high humidity, whole maize plant requires to be dehydrated before inclusion in pelleted diets for rabbits and the maturity stage is important, since the dry matter (DM) content of maize plant increases from 23 to 37% during the maturing process of the grain (Abreu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thompson (1968) found that a group of exotic and semi-exotic populations yielded on average 28% more digestible dry matter than adapted hybrids, and Stuber (1986) suggested that some semi-exotic materials might be suitable for silage, given their good grain production and great vegetative development. More recently, Bertoia (2001) noted that landraces with no history of breeding for grain production generated crosses with good forage potential, whereas inbred lines from the North American Corn Belt did not demonstrate potential for enhanced stover yield and quality when compared with inbred lines from Argentine germplasm (Bertoia et al, 2002).…”
mentioning
confidence: 99%